Suu Balm: From lead user innovation to rapid growth - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2021)
This case is set in 2020 and talks about a start-up pharmaceutical marketing company - Good Pharma – based in Singapore. One of the first products the firm had embarked on marketing was Suu Balm, a cream for dry and eczema-prone skin, which had been formulated by a lead user - Dr Tey Hong Liang (Dr. Tey) from Singapore’s renowned National Skin Centre (NSC). As a lead user innovation, Suu Balm had gone through extensive licensing negotiations before launch and took some time to see market success. The Suu Balm cream was a menthol based formulation to help relieve itch from dry skin conditions. Initially, the cream was sold online and to government and private dermatologists and general practitioners directly. Later the company approached retail pharmacy stores like Guardian and Watsons to distribute the product and saw spiralling sales growth at an average of 180% a year. The firm expanded beyond Singapore to other Asian countries, the U.K. and Ireland, by collaborating with both physical and online retail stores. However, it faced some hiccups in its collaborations with physical stores in Ireland and U.K. and quickly shrank its expansion in these countries after incurring some losses. Dr. Tey had also noted an increasing demand for additional products from his patient visits, which led to the expansion of the Suu Balm brand to include hair care, facial care, and products suitable for children. Effective product and geographical expansion strategies fuelled further business growth, and by 2019, Suu Balm’s retail sales had exceeded US$3.69 million in its home market alone. However, Good Pharma wanted to expand beyond collaborations and launch its own products in the market moving forward. Could lead user innovation still be a viable strategy for Good Pharma’s next growth stage as a start-up company? The case helps students deliberate on start-up growth strategies, licensing and pricing strategy challenges, and the benefits and limitations of lead user innovation.